Peranan Dan Penggunaan Database Dalam Perusahaan Developer PT Arjuna Land City Group - Nurfadillah Najwa Faraiddin; Muhammad Irwan Padli Nasution (Universitas Katolik Widya Karya Malang, 2023)
The database is a collection of data items related to each other and organized based on a certain system or structure. They are stored in computer hardware and software and are used to process data (updated, retrieved, processed by certain calculations and deleted) with a specific purpose. In a database company it is very useful, one of which is PT Arjuna Land City Group. For them the database is very useful for providing information to companies about consumers, marketing, availability of goods, prices, consumer payments, and many others. The purpose of this research is to provide information to readers on the role and use of databases in a company, one of which is PT Arjuna Land City Group, which is in charge of business in the developer sector. The results of this research are the results of my interview with one of the company's employees along with examples from the database they use.